Science in progress. (New Haven, Yale University Press., 1938)
Vols. for <1964-> contain national lectureships of the Society of Sigma Xi and the Scientific Research Society of America.
Also issued online.
SERBIB/SERLOC merged record
Keywords: Science -- Periodicals; Research -- Periodicals; Research -- Periodicals; Science -- Periodicals; Sciences -- Collections; Recherche -- Collections